BÖLEBADET - Bergström, Klara (My University, 2023)
This thesis explores how a public river bath in Umeå, Sweden, can be designed to accommodate the traditional Nordic bathing rituals, and how architecture that encourages sensory experience can create a stronger connection to the natural surroundings. Located close to the city centre of Umeå, about 2 kilometres upstream, lies a small set of islets called Bölesholmarna. These islets are part of a recreational walking trail connecting the north and the south side of the river. The cold bathing facility will float just outside of the western point of the islets and can be viewed as an extension of this trail, thereby connecting the bath to the busy city centre through another outdoor activity. The design of the building creates a connection with the surrounding environment, directing the attention to the river and encouraging visitors to slow down and appreciate the natural beauty of the area. The history of log driving on the site will be explored and used as reference in the building’s façade. The design of the building is based on the notion that partaking in a ritual can strengthen the connection to place through repetition and sensory experiences. By designing for the traditional act of sauna bathing, a deeper connection between people and their environment can be evoked. The thesis will therefore cover the background and history of the Swedish sauna bathing, as well as aim to describe why it has become such an important and integral part of our culture. By mapping out its historical and cultural importance, the goal of the thesis is to use it as a design tool, and through research by design propose a space meant for the experience of the ritual. And by doing so further enhancing our presence in nature, in order to take better care of our planet and ourselves.
Keywords: sauna | cold bathing | ritual | culture | sensory experience |